Growth and change in Britain's development NGO sector (2009–2015). Issue 6 (17th August 2020) - Banks, Nicola; Brockington, Dan
ABSTRACT : A paucity of systematic research into development NGO sectors means that we have underestimated their contributions to international development. In 2015 Britain's development NGOs spent nearly £7 billion, equivalent to over half of the UK government's Official Development Assistance (ODA) that year. Mapping the sector reveals its size and significance and gives new insight into its structural composition and how this it is influenced by changes to the funding landscape. Alongside new insights into an influential sector, this work highlights the importance of innovative research methods and techniques for a more systematic understanding of development NGOs globally.